O efeito dos gastos em pesquisa e desenvolvimento nas ações das empresas petrolíferas - Almeida, Willian Freitas de (2013)
This work aims to identify the relationship between R&D expenditure and prices per share of integrated oil and gas companies on the NY SE. Return of investiment on R&D spending can be seen when research results are applied to production processes, increasing operational efficiency, reduc ing costs and creating new products. This usage may be a channel to share pric e variations. Whereas spendings in R&D have a long term effect, the analisys includ ed contemporary, lagged and annual aggregate R&D expenditure data. Results point to a positive relation between R&D expenditure and share prices. Share price varia tions were better explained by lagged data, and the positive relation becomes stat istically significant when five-years aggregates are employed. This outcome confirms the long term effect of this type of expenditure.